Interference investigations of liquid crystal–polymer composites structure - Maksymyak, Peter; Negrych, Andriy; Dolgov, Leonid; Yaroshchuk, Oleg (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
The methods of correlation optics are for the first time applied to study the structure of liquid crystal–polymer (LC–P) composites. Their phase correlation function (PCF) was obtained considering LC–P composite as a random phase screen. The amplitude of PCF contains information about the number of LC domains and structure of LC director inside of them, while a half-width of this function is connected with the size of these domains. In good agreement with previous studies by SEM technique we detected a monotone decrease of LC domains with polymer concentration. When applying the electric field, for the samples with φP > 35 vol.% (PDLC morphology), the amplitude of PCF is monotonic. On the contrary, if φP < 35 vol.% (PNLC morphology) the amplitude of PCF is non-monotonic and, depending on the applied voltage, goes through maximum.
Optica Applicata, Vol. 39, 2009, nr 3, s. 571-578
Keywords: optyka; liquid crystal; PDLC; light scattering; correlation optics; phase correlation function; morphology